Clinical characteristics of patients requiring lung transplantation referral in national cystic fibrosis registry data - Onay, Zeynep Reyhan; Eyuboglu, Tugba Sismanlar; Aslan, Ayse Tana; Gursoy, Tugba Ramasli; Yalcin, Ebru; Kiper, Nural; Dogru, Deniz (Turkish J Pediatrics, 2023)
Background. We aimed to determine the number of cystic fibrosis (CF) patients recorded in the Cystic Fibrosis Registry of Turkiye (CFRT) who were in need of lung transplantation (LT) referral and examine clinical differences between patients who were LT candidates due to rapid forced expiratory volume in one second (FEV1) decline and LT candidates without rapid FEV1 decline in the last year to identify a preventable cause in patients with such rapid FEV1 decline. Methods. All CF patients recorded in the CFRT in 2018 were evaluated in terms of LT. Patients were divided into those with FEV1 below 50% and in need of LT due to a decrease of 20% or more in the previous year (Group 1) and those who did not have FEV1 decline of more than 20% in the previous year but had other indications for LT (Group 2). Demographic and clinical features were compared between the two groups. Results. Of 1488 patients registered in CFRT, 58 had a need for LT. Twenty patients were included in Group 1 and others in Group 2. Our findings did not reveal any significant variations in treatment, chronic infection status, or complications between the two groups. The average weight z-score was significantly higher in Group 1. Positive correlations were detected between weight z-score and FEV1 in 2017 in Group 1 and between FEV1 values in 2017 and 2018 in Group 2. Conclusions. There appears to be a relationship between the nutritional status and weight z-scores of CF patients and pulmonary function, which may indirectly affect the need for lung transplantation referral.
Keywords: cystic fibrosis; lung transplantation; registry